Analisis Resepsi Khalayak Terhadap Strategi Kampanye ‘Gemoy’ dalam Gerakan Politik Prabowo Subiyanto Pada Pemilihan Presiden 2024 (Studi Pada Khalayak Pengguna Media Sosial TikTok) - Vallene Laurencia Viendry Sujarwo; Cosmas Gatot Haryono (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This study examines the reception of voters across generations (Gen X, Y, Z) who are active TikTok users toward the “Gemoy” campaign strategy of Prabowo-Gibran in the 2024 Presidential Election, employing Alfred Schutz’s phenomenological approach. Data were collected through interviews with active TikTok voters of various ages and analysis of engagement metrics, including 1.19 billion views, 73.6 million likes, and 3.36 million comments on campaign content. The findings reveal diverse responses, ranging from high enthusiasm and engagement among young voters to more critical attitudes regarding substance in other groups. Visual and humorous strategies were found effective in fostering emotional connection and expanding the reach of political messages in the digital era. This study highlights new dynamics in Indonesian political communication, where entertainment- and image-based approaches on social media contribute to shifts in voter behavior and patterns of political engagement among the younger generation.